Strategi Komunikasi Humas dalam Memperbaiki Citra Kementerian Pemuda dan Olahraga - Meilissa Elviani; N R Nadya Karina (CARAKA : Indonesia Journal of Communication, 2020)
The red-handed arrest of Youth and Sports Ministry officials by the Corruption Eradication Commission at the end of 2018 once again put the government institution on the spotlight.  Corruption cases have always been under the spotlight particularly when they involve government institutions. The graft case involving officials of the Youth and Sports Ministry prompted its public relations service to adopt an appropriate strategy to prevent its image from deteriorating and instead to improve it. This research aims to see the strategy adopted by the ministry’s public relations service to address a crisis of public confidence. This research uses a qualitative method by collecting data through documentation studies.  Hopefully, this research will serve as a reference for other institutions that may face the same problem.